A new genus and two new species of unarmed hymenolepidid cestodes (Cestoda: Hymenolepididae) from geomyid rodents in Mexico and Costa Rica - Gardner, Scott L.; Dursahinhan, Altangerel T.; Campbell, Mariel L.; Rácz, S. Elizabeth (Zootaxa, 2020)
Two new cestodes of the family Hymenolepididae are described from two species of rodents of the family Geomyidae collected in Mexico and Costa Rica. One new species of Hymenolepis is described from Cratogeomys planiceps Merriam 1895 from near Toluca, Mexico and another that we allocate to a new genus is described from Heterogeomys heterodus (Peters, 1865) from near Irazú Volcano, Costa Rica. Hymenolepis s. str. includes those Hymenolepididae with an apical organ, with no hooks on suckers or apical organ, and three testes. Hobergia irazuensis n. gen., n. sp. includes a hymenolepidid with an apical organ, unarmed scolex, small pockets termed foveolae, in which the suckers completely retract, and extremely bi-lobed ovary. Multivariate morphometric analysis showed good separation of these species from all other hymenolepidids possessing an apical organ and lacking a well developed rostellum and rostellar hooks in the Nearctic and Neotropical regions.